2013
DOI: 10.1128/aac.00723-13
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis Comparing Two Approaches for Empirical Antifungal Therapy in Hematological Patients with Persistent Febrile Neutropenia

Abstract: e New approaches of empirical antifungal therapy (EAT) in selected hematological patients with persistent febrile neutropenia (PFN) have been proposed in recent years, but their cost-effectiveness has not been studied. The aim of this study was to compare the cost-effectiveness of two different approaches of EAT in hematological patients with PFN: the diagnosis-driven antifungal therapy (DDAT) approach versus the standard approach of EAT. A decision tree to assess the cost-effectiveness of both approaches was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Most of these reports, however, only examined preemptive during periods of neutropenia and/or were performed in healthcare systems outside the US . Additionally, GM testing was typically triggered by fever rather than being used as a surveillance tool, which also limits comparisons to our analysis . Of the published reports most similar to our study, two assumed a lower unit cost per GM test .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Most of these reports, however, only examined preemptive during periods of neutropenia and/or were performed in healthcare systems outside the US . Additionally, GM testing was typically triggered by fever rather than being used as a surveillance tool, which also limits comparisons to our analysis . Of the published reports most similar to our study, two assumed a lower unit cost per GM test .…”
Section: Discussionmentioning
confidence: 91%
“…Previous cost‐effectiveness studies comparing empiric and preemptive treatment have also generally found preemptive to be cost saving . Most of these reports, however, only examined preemptive during periods of neutropenia and/or were performed in healthcare systems outside the US . Additionally, GM testing was typically triggered by fever rather than being used as a surveillance tool, which also limits comparisons to our analysis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nor were any studies found that compared the efficacy of other antifungal therapy strategies in IA or in other indications in galactomannan-positive patients. In published studies, only the unit cost of the galactomannan test was assessed, and not its diagnostic role as a possible determinant of the cost-effectiveness of IA therapy 36,37. No costs were considered for additional diagnostic tests given as part of a full diagnostic workup or as follow-up to galactomannan antigen testing, under the assumption that these costs would not be substantial.…”
Section: Discussionmentioning
confidence: 99%
“…A cost‐effectiveness analysis comparing this DDAT approach with the standard approach of EATS showed that the economic advantage for the former per persistent febrile neutropenic episode was $5879 (33%) . The average cost‐effectiveness per episode was $32 671 for the DDAT approach compared with $52 479 for the EAT approach.…”
Section: The Particular Case Of High‐risk Neutropenic Patientsmentioning
confidence: 99%